Using Coriolis mass flowmeter for wet gas metering - Geng, Yanfeng; Yeung, Hoi; Cao, Yi; Xing, Lanchang; Zhu, Hao; Drahm, Wolfgang (Institute of Measurement & Control, 2010)
Established wet gas metering techniques are typically based on differential pressure devices, and their measurement accuracy is still unsatisfactory to natural gas industry. Coriolis mass flowmeter (CMF) is the most superior flow measurement technology at now, it can provide mass flowrate and density output simultaneously. Putting CMF into wet gas metering may be a reasonable and high accuracy solution to natural gas industry demands. The problems and advantages of CMF in gas-liquid two-phase flow metering has been analyzed, a serious experiments has been carried out to test the possibility and feasibility of CMF as wet gas meter. Experimental conclusions are promising，CMF can work properly in wet gas metering condition, and the repeatability test of CMF is perfect, and the relationship between the true mass flowrate and CMF readings are almost linear. When gas flowrate is kept to a constant, CMF can follow the variations of liquid flowrate accurately. At last, some open problems deserving further investigation are propose